2014
DOI: 10.1021/ic5008632
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of π Contacts between Metal Ions and Fluorophores on the Fluorescence of PET Sensors: Implications for Sensor Design for Cations and Anions

Abstract: The idea that M···C π contacts between diamagnetic heavy metal ions such as Pb(II), Ag(I), Pd(II), or Hg(II) and the anthracenyl fluorophore of adpa ((N-(9-anthracenylmethyl)-N-(2-pyridinylmethyl)-2-pyridinemethanamine) are responsible for quenching the fluorescence of the complexes of these metal ions with adpa is explored crystallographically. The structures of [Pb(adpa)(NO3)2] (1), [Ag(adpa)NO3] (2), [Pd(adpa)NO3]NO3 (3), [Zn(adpa)(NO3)2] (4), and [Cd(adpa)Br2] (5) are reported. The π contacts with the fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 59 publications
3
69
0
Order By: Relevance
“…Of particular interest is the presence of two π contacts between the Ag I ion and the dimethoxycoumarin fluorophore, of 3.083 and 3.095 Å. The structure of the Ag I (cdpa) complex strongly resembles that of the Ag I (adpa) complex, except that the latter has a η 1 contact with the anthracenyl fluorophore of adpa, with an Ag···C distance of 3.016 Å, 3 whereas the Ag I ion in its cdpa complex has a η 2 π contact. The presence of π contacts between the coordinated Ag I and the fluorophore of cdpa is consistent with the π-contact model of quenching of the fluorescence, in that coordination of Ag I to cdpa leads to strong quenching of the fluorescence, as also occurs with the adpa complex, where an Ag···C π contact is present.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Of particular interest is the presence of two π contacts between the Ag I ion and the dimethoxycoumarin fluorophore, of 3.083 and 3.095 Å. The structure of the Ag I (cdpa) complex strongly resembles that of the Ag I (adpa) complex, except that the latter has a η 1 contact with the anthracenyl fluorophore of adpa, with an Ag···C distance of 3.016 Å, 3 whereas the Ag I ion in its cdpa complex has a η 2 π contact. The presence of π contacts between the coordinated Ag I and the fluorophore of cdpa is consistent with the π-contact model of quenching of the fluorescence, in that coordination of Ag I to cdpa leads to strong quenching of the fluorescence, as also occurs with the adpa complex, where an Ag···C π contact is present.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Also shown in Table 9 for comparison are the formation constants for dpa (in aqueous solution) 42 and adpa (in 50% MeOH/H 2 O) complexes. 1,3 The fact that the log K 1 values for the dpa complexes are reported in an aqueous solution should not make a great difference because it has been found that log K 1 values for 50% MeOH/H 2 O and H 2 O are quite similar. 5 One sees that the order of stability for most metal ions with the three ligands is dpa > adpa > cdpa.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…could be better exhibited by fluorescence titrations. After addition of Al 3+ , the fluorescence intensity increased significantly which was because that the chelation of the nitrogen atom of the -C=N group with Al 3+ resulted in the efficient inhibition for the PET process of the lone pair electrons on N of the -C=N-group[35][36][37][38].3.3. The sensing mechanism was .proposed base on the chelation as shown in Scheme 2.…”
mentioning
confidence: 99%